Reliability modeling and assessment of isolated microgrid considering influences of frequency control - Guo, Jing (2019)
Frequency control of isolated microgrid (MG) relies heavily on a safe and reliable cyber system. Random failures of cyber elements may cause the malfunction of the frequency control, resulting in reliability issues, e.g., load shedding or generation curtailment. A reliability modeling and assessment method for isolated MG is proposed, considering the influence of frequency control from cyber physical system perspectives. The frequency control process is modeled to establish the interdependencies between a cyber system and physical system within MGs. An assessment method is proposed to quantify the impacts of cyber element failures based on the frequency control models. A set of novel reliability index is defined to illustrate impacts of frequency control malfunction on the MG reliability. The sequential Monte Carlo simulation method is adopted to assess the reliability of MGs considering the malfunction of frequency control. The effectiveness of proposed models and indices is demonstrated by the case studies on an isolated MG. The test results indicate that the frequency control malfunction caused by the failures of cyber elements has a great impact on MG reliability. This research can provide technical support for the planning and operation of isolated MGs.